(untitled) (Revista Direito em Debate, 2022)
This paper aims to analyze the decision of the UN’s Committee Against Torture, from August 2019, that found Bosnia guilty of sexual violence that occured during the Yugoslav war. Considering that sexual crimes in armed conflicts are predominantly an instrument of war, instead of a consequence, this paper firstly analyzes the evolution of international legislation and precedents on the subject, using a descriptive method. Secondly, it considers the Committee’s decision, which includes the case summary, competence discussions and the impacts of the decision on the development of the sexual violence subject in international law. This second part is based on a qualitative method. Among the conclusions, the Committee’s decision appears as a historical and legal milestone when it comes to sexual violence in armed conflicts, revealing not only a new permanent institution to judge similar cases, but also condemning the State and providing a more effective way to repair the damage caused to the victims, compared with the other international courts.